KESETARAAN GENDER DAN KINERJA NON FINANSIAL PADA PERUSAHAAN PUBLIK DI INDONESIA - Yudha Adhitya; Nadia Asandimitra Haryono; Harlina Meidiaswati (Universitas Negeri Surabaya, 2026)
The objective of this study is to examine the influence of gender equality on corporate ESG performance among publicly listed companies in Indonesia. This research employs an explanatory quantitative approach by analyzing secondary data obtained from the annual reports and sustainability reports of 21 companies included in the ESG Leaders Index of the Indonesia Stock Exchange as of April 24, 2025, over a four-year period (2021–2024), using panel data regression. The findings indicate that gender equality, proxied by the proportion of female directors on the board, has a positive effect on overall ESG performance as well as on environmental and social performance. However, its effect on governance performance is negative. The minimum threshold of female representation on the board does not influence ESG performance or any of its individual dimensions. These results reinforce stakeholder theory and resource dependence theory. The differing result regarding critical mass theory may be attributed to variations in country-specific conditions. This study also provides insights for publicly listed companies in Indonesia seeking to enhance their ESG performance by offering greater opportunities for women to serve on corporate boards.